Future-Proofing Adult Learning in Berlin, Germany. - OECD. (Organization for Economic Cooperation & Development, 2022)
After a long period of employment growth that led to the lowest unemployment rate since the German reunification, Berlin's labour market is now tightening. Accelerated by the COVID-19 pandemic, global labour market megatrends such as the automation of production processes and the increasingly advanced digital skills required to perform many jobs pose new challenges to Berlin's policymakers.